THE CONTROLLING SYSTEM OF RESEARCH UNIVERSITY - Irina E. Nikulina (Высшее образование в России)
Strengthening of competition among universities requires special demands on the quality of the scientific and educational process and university management system. Within the existing system of university quality management it is important to consider controlling. Controlling system acts as a conceptual and methodological basis for integration and coordination of university management, as an instrument of formation and future accounting feedback in the process of governance. For research universities it is particularly important to establish a system of controlling considering a large number of software development activities, as well as indicators of their achievement.